2012
DOI: 10.1158/1535-7163.mct-11-0613
|View full text |Cite
|
Sign up to set email alerts
|

CK2 Inhibitor CX-4945 Suppresses DNA Repair Response Triggered by DNA-Targeted Anticancer Drugs and Augments Efficacy: Mechanistic Rationale for Drug Combination Therapy

Abstract: Drug combination therapies are commonly used for the treatment of cancers to increase therapeutic efficacy, reduce toxicity, and decrease the incidence of drug resistance. Although drug combination therapies were originally devised primarily by empirical methods, the increased understanding of drug mechanisms and the pathways they modulate provides a unique opportunity to design combinations that are based on mechanistic rationale. We have identified protein kinase CK2 as a promising therapeutic target for com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
95
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 44 publications
9
95
0
1
Order By: Relevance
“…Antiproliferative activity was 23% to 38% higher than Bliss additivity when CX-4945 was added to cells after treatment with gemcitabine or cisplatin. These treatments were also accompanied by decreased phosphorylation of the CSNK2 substrates XRCC1 and MDC1 and accumulation of single-stranded and double-stranded DNA breaks (32). These data are in agreement with the observations of CSNK2 localizing to the nucleus in response to DSBs and for the role of CSNK2 in the DDR and DNA repair mechanisms (20,25,33,34).…”
Section: Cx-4945: An Atp-competitive Csnk2 Inhibitor In Clinical Trialssupporting
confidence: 89%
“…Antiproliferative activity was 23% to 38% higher than Bliss additivity when CX-4945 was added to cells after treatment with gemcitabine or cisplatin. These treatments were also accompanied by decreased phosphorylation of the CSNK2 substrates XRCC1 and MDC1 and accumulation of single-stranded and double-stranded DNA breaks (32). These data are in agreement with the observations of CSNK2 localizing to the nucleus in response to DSBs and for the role of CSNK2 in the DDR and DNA repair mechanisms (20,25,33,34).…”
Section: Cx-4945: An Atp-competitive Csnk2 Inhibitor In Clinical Trialssupporting
confidence: 89%
“…However, the evidence of DNA repair gene on ovarian cancer patients with adjuvant chemotherapy in lacking. Several experimental studies reported the association between XRCC1 gene polymorphism and ovarian cancer risk, and the results are conflicting (Jakubowska et al, 2010;Siddiqui-Jain et al, 2012). Two studies conducted in Korea and Russian reported the association of XRCC1 Arg194Trp and XRCC1Arg399Gln gene polymorphisms with survival of ovarian cancer with chemotherapy (Kim et al, 2009;Khrunin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence of DNA repair gene on ovarian cancer in lacking. Only several experimental studies reported the association between XRCC1 gene polymorphism and ovarian cancer risk, and the results are conflicting (Jakubowska et al, 2010;Kudo et al, 2012;Siddiqui-Jain et al, 2012;). A study reported inactivation of XRCC1 could influence the effect of platinum-based chemotherapeutics in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%